Experiences of Psychosocial Support in Group Rehabilitation Interventions from Adults with Chronic Conditions – A Qualitative Systematic Review - Jenny Mäkeläinen; Ulla Jämsä; Anne Oikarinen; Maria Kääriäinen; Heidi Siira (Patient Experience Journal)
Aims and objectives: Psychosocial support is essential in group rehabilitation interventions aiming at supporting adaptation to chronic illness and disability. Aim was to synthesize qualitative evidence on how adults with chronic conditions experience psychosocial support in group rehabilitation interventions. Materials and Methods: Four databases (CINAHL, Medic, Pubmed, Scopus) were searched for qualitative studies published between 2009-2022. Study selection and critical appraisal were independently performed by two authors using the JBI Critical Appraisal Checklist. Study selection and critical appraisal were independently performed by two authors. Data were synthesized through inductive content analysis. Results: The findings from nine studies were synthesized into 105 sub-categories, 15 categories and to six main categories: 1) Management of life; 2) Reflective communication; 3) Group process; 4) Invaluable peer support; 5) Professional as a competent human trainer; and 6) Process of relief. Conclusion: Psychosocial support in group rehabilitation interventions can provide adequate social support and a basis for self-management. Both healthcare professionals and peers have invaluable roles in helping patients with chronic conditions adapt to their life situation. Interventions should facilitate knowledge sharing and help patients take responsibility for self-management. Furthermore, participants should be able to choose the topics of the program. Healthcare professionals have an important role in initiating conversations about topics which may be taboo. Professionals should recognize participants’ individualized needs for information and support, and foster group dynamics by supporting open communication and reflection.